2020
DOI: 10.4103/tjo.tjo_28_20
|View full text |Cite
|
Sign up to set email alerts
|

Orbital hybrid peripheral nerve sheath tumors

Abstract: Hybrid peripheral nerve sheath tumors (HPNST) are recently classified tumors from the World Health Organization Classification of soft tissue tumors that display combined features of more than one peripheral nerve sheath tumor. Acknowledgment is important because of its association with the development of neurofibromatosis type 1, type 2, and schwannomatosis. Orbital involvement is rare and only six cases of HPNST have been documented on literature. This article serves to review the pathophysiology, clinical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…1,7,[10][11][12] Neurofibroma-schwannoma features neurofibroma comprising a mixed population of fibroblasts, Schwann cells, and perineurial cells in a collagenous and occasionally myxoid background and cellular nodules composed of monomorphic Schwann cells in a palisaded Antoni A arrangement with Verocay body formation. 2,4,12,13 Hybrid neurofibroma-perineurioma, the least frequent HPNST subtype, has been described in association with NF1. This tumor is composed of a plexiform neurofibroma with areas of perineurial differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,7,[10][11][12] Neurofibroma-schwannoma features neurofibroma comprising a mixed population of fibroblasts, Schwann cells, and perineurial cells in a collagenous and occasionally myxoid background and cellular nodules composed of monomorphic Schwann cells in a palisaded Antoni A arrangement with Verocay body formation. 2,4,12,13 Hybrid neurofibroma-perineurioma, the least frequent HPNST subtype, has been described in association with NF1. This tumor is composed of a plexiform neurofibroma with areas of perineurial differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…1 HPNST demonstrates a biphasic pattern containing mixed components of neurofibroma, schwannoma, and perineurioma with either a clear transition between cell types or an intermingling of cell types. 2 Several subtypes of HPNST have been identified, including neurofibroma-schwannoma, schwannoma-perineurioma, and neurofibroma-perineurioma. [2][3][4] Orbital involvement of HPNST is extremely rare with only 7 cases of all types reported in the literature.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In 1768, Akenside first published a scientific description of a patient with multiple tumors involving the peripheral nerves[ 1 ]. Over ten decades later, von Recklinghausen demonstrated that neurofibromas belong to a single nerve[ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 They rarely arise from the orbit. [1][2][3] This video shows the microsurgical resection of HNST involving both the orbit and lateral wall of the cavernous sinus. A 43-yr-old woman presented with 1-yr history of a slowly growing painless mass in her left medial eyelid.…”
mentioning
confidence: 99%